The Late Spanish Scholastics – Part 2 - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
This text deals with the development of social and economic thought of the late Scholastics, Luis de Molina until the decline of the School of Salamanca. The analysis begins with the monetary thought in Molina, Suárez and Mariana, continues with the doctrine of just price in Lessius and concludes with the theory of subjective value in Lugo. The Spanish scholastic thought is analyzed taking into account the background of theological controversies and historical events of the period, until the decline with the Reformation and the philosophical interpretations raised by the advent of modern science.